1999
DOI: 10.2307/2640711
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and Virulence Structure in Two Linum marginale-Melampsora lini Host-Pathogen Metapopulations with Different Mating Systems

Abstract: Different patterns of resistance to six pathotypes of Melampsora lini were detected in 11 populations of Linum marginale distributed across two metapopulations. The two metapopulations (mountains and plains of New South Wales, Australia) differed in the annual cycle of disease development, which barely overlapped, and in the growth cycle and mating system of the host. Host populations in the mountains metapopulation were highly inbred, whereas those on the plains showed appreciable levels of outcrossing. Withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 18 publications
2
53
0
Order By: Relevance
“…It will be interesting to determine whether genetic variation in R genes is predominantly maintained by combining many R genes in the same genotype, or by assorting functional genes into simple genotypes and maintaining them in heterogeneous populations. The latter has been suggested by two studies of wild groundsel (Senecio vulgaris) and flax 55,56 . Detailed molecular genetic analyses have yet to be pursued in these pathosystems; however, functional NB-LRR genes already characterized in flax provide exciting examples for future studies of wild flax populations.…”
Section: Box 2 | Evolution Of R Genes In Local Populationsmentioning
confidence: 89%
“…It will be interesting to determine whether genetic variation in R genes is predominantly maintained by combining many R genes in the same genotype, or by assorting functional genes into simple genotypes and maintaining them in heterogeneous populations. The latter has been suggested by two studies of wild groundsel (Senecio vulgaris) and flax 55,56 . Detailed molecular genetic analyses have yet to be pursued in these pathosystems; however, functional NB-LRR genes already characterized in flax provide exciting examples for future studies of wild flax populations.…”
Section: Box 2 | Evolution Of R Genes In Local Populationsmentioning
confidence: 89%
“…Such among-population processes might promote loss of genetic diversity within parasite populations and generate among-population genetic differences (e.g. through genetic drift), as has been observed for the biotrophic rust pathogen Melampsora lini infecting wild Australian flax Linum marginale , which is typified by ‘boom-and-bust’ epidemic dynamics [23,24]. By contrast, pathogens able to infect multiple hosts or survive in the absence of a host are unlikely to regularly experience such extreme levels of population stochasticity, and thus should maintain comparatively higher levels of within-population genetic variation.…”
Section: Impacts Of Parasite Life History On Population Demography Anmentioning
confidence: 99%
“…In the interaction between L. marginale and M. lini , populations of Linum located in the mountains and plains regions of New South Wales of Australia are separated by several hundred kilometres. Detailed studies of host resistance structure within and between these regions showed large differences in average resistance, both among populations within the mountains and plains areas, as well as between regions (Burdon et al 1999). Levels of within-family heterogeneity in disease resistance in the mountain populations were low while heterogeneity within family lines was much more frequent in the plains.…”
Section: Patterns Of Resistance At Different Spatial Scalesmentioning
confidence: 99%